Parameter Analysis of Anion Exchange Membrane Water Electrolysis System by Numerical Simulation - Shing-Cheng Chang; Ru-En Gu; Yen-Hsin Chan (Energies)
Anion exchange membrane electrolysis, which combines the advantages of both alkaline electrolysis and proton-exchange membrane electrolysis, is a promising technology to reduce the cost of hydrogen production. The present work focused on the study of the electrochemical phenomena of AEM electrolysis and the investigation of the key factors of the AEM hydrogen production system. The numerical model is established according to electrochemical reactions, polarization phenomena, and the power consumption of the balance of plant components of the system. The effects of operation parameters, including the temperature and hydrogen pressure of the electrolyzer, electrolyte concentration, and hydrogen supply pressure on the energy efficiency are studied. The basic electrochemical phenomena of AEM water electrolysis cells are analyzed by simulations of reversible potential and activation, and ohmic and concentration polarizations. The results reveal that increasing the operating temperature and hydrogen production pressure of the AEM electrolyzer has positive effects on the system’s efficiency. By conducting an optimization analysis of the electrolyzer temperature—which uses the heat energy generated by the electrochemical reaction of the electrolyzer to minimize the power consumption of the electrolyte pump and heater—the AEM system with an electrolyzer operating at 328 K and 30 bar can deliver hydrogen of pressure up to 200 bar under an energy efficiency of 56.4%.